2015
DOI: 10.1007/s10637-015-0251-5
|View full text |Cite
|
Sign up to set email alerts
|

Dose-finding study of hepatic arterial infusion of irinotecan-based treatment in patients with advanced cancers metastatic to the liver

Abstract: BACKGROUND Liver metastases are associated with a poor prognosis. We investigated the use of hepatic arterial infusion (HAI) of irinotecan combination therapy in patients with liver metastases. PATIENTS AND METHODS Patients with histologically confirmed advanced cancer with liver metastases that was refractory to standard therapy were eligible. A standard “3+3” phase I study design was used to determine the dose-limiting toxicity (DLT) and the maximum tolerated dose (MTD). Three cohorts were evaluated: HAI o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Trials on two different—more regional infusion methods—have been conducted. First, locoregional therapy with irinotecan infusion into the hepatic artery has been evaluated for the treatment of unresectable liver metastases; different irinotecan formulations have been demonstrated to be safe and effective [ 95 , 96 ]. This approach resulted in lower systemic exposure to irinotecan and an increased conversion of irinotecan into SN-38 compared with intravenously administered irinotecan [ 97 ].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Trials on two different—more regional infusion methods—have been conducted. First, locoregional therapy with irinotecan infusion into the hepatic artery has been evaluated for the treatment of unresectable liver metastases; different irinotecan formulations have been demonstrated to be safe and effective [ 95 , 96 ]. This approach resulted in lower systemic exposure to irinotecan and an increased conversion of irinotecan into SN-38 compared with intravenously administered irinotecan [ 97 ].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…These patients took docetaxel and two anti-HER-2 agents, trastuzumab and pertuzumab, along with surgery to resect the metastatic liver part [169]. Another option for treating patients with liver metastasis is to administer a combination of drugs via hepatic arterial infusion (HAI): irinotecan, bevacizumab, and oxaliplatin combined with bevacizumab or cetuximab [170] have been used. In colorectal cancer patients with liver and lung metastases, completely resecting metastases in both organs offers the best survival results.…”
Section: Metastasis In Target Organsmentioning
confidence: 99%
“…However, the combination of systemic bevacizumab with intra-arterial of floxuridine was observed to bear a higher risk of biliary tract damage [86], without significantly improving outcomes [87]. Notwithstanding, other phase I studies have not reported an increment in toxicity associating intravenous bevacizumab and hepatic artery infusion of other cytotoxic drugs [88][89][90][91]. This therapeutic option deserves therefore further testing.…”
Section: Open Questionsmentioning
confidence: 99%